Visna virus RNA synthesis. - Brahic, M (1977)
Visna is a classical slow infection in which virus characteristically persists in the face of the host immune response. The agent of this disease belongs to the retravirus group. The persistence of infection and the slow spread of virus are at least in part a consequence of restriction of the expression of virus genetic information in tissues of an infected animal (A. T. Haase et al., Science 195:175-177, 1977), but the point at which the virus life cycle is interrupted in vivo and the mechanism of restriction are unknown. We have embarked on a molecular analysis of restriction, focusing first on transcription. In this paper we have established the levels of viral RNA synthesis under permissive conditions, as a base line for subsequent studies in vivo. We show that (i) uninfected cells do not contain RNA sequences related to the visna virus genome, (ii) parental RNA is rapidly transported to the nucleus of the infected cell, (iii) virus RNA is synthesized in the nucleus and then transported to the cytoplasm (iv) synthesis of RNA proceeds mostly exponentially to reach levels of about 4,000 copies per cell at the end of the growth cycle, (v) nuclear and cytoplasmic RNA sediment in two size classes, 35S and 10-20S, (vi) viral mRNA has the same polarity as genome RNA and also sediments in two size classes of 35S and 10-20S.